OF REMUNERATION: ORGANIZATIONAL AND AN ANALYSIS - Дорогань-Писаренко, Л. О. (Scientific Progress & Innovations, 2014)
The article highlights the current state of civil service pay. Analysis of the experience of foreign countries in the public service. A system of payment to settle civil servants by restructuring their income. The necessity of unification of the difference in salaries and wages of employees of various levels of government. The basic directions of perfection of the civil servants and their pay.